2011
DOI: 10.1073/pnas.1114207108
|View full text |Cite
|
Sign up to set email alerts
|

Formation of buckminsterfullerene (C 60 ) in interstellar space

Abstract: Buckminsterfullerene (C 60 ) was recently confirmed as the largest molecule identified in space. However, it remains unclear how and where this molecule is formed. It is generally believed that C 60 is formed from the buildup of small carbonaceous compounds in the hot and dense envelopes of evolved stars. Analyzing infrared observations, obtained by Spitzer and Herschel, we found that C 60 is efficiently formed in the tenuous and cold environment of an interstellar cloud illuminated by strong ultraviolet (UV) … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
277
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 313 publications
(294 citation statements)
references
References 45 publications
16
277
1
Order By: Relevance
“…This situation leaves small patches of graphene weakly bound to a H-saturated substrate, ready to be ejected by thermal or photoexcitation processes. These molecules could be the origin of the recently proposed top-down interstellar carbon chemistry 29 and the reason why SiC is abundant in evolved stars but normally gone in the ISM 30 . Figure 3a,b shows some regions of the surface that have been heavily etched.…”
Section: Resultsmentioning
confidence: 99%
“…This situation leaves small patches of graphene weakly bound to a H-saturated substrate, ready to be ejected by thermal or photoexcitation processes. These molecules could be the origin of the recently proposed top-down interstellar carbon chemistry 29 and the reason why SiC is abundant in evolved stars but normally gone in the ISM 30 . Figure 3a,b shows some regions of the surface that have been heavily etched.…”
Section: Resultsmentioning
confidence: 99%
“…As the unimolecular dissociation rate depends exponentially on the internal excitation temperature and, therefore, in a given radiation field, on the size of the PAH, PAHs with a size smaller than a critical size are fully stripped of all their H (and do not contribute emission in any C-H mode), while PAHs larger than this size are fully hydrogenated. Small fully dehydrogenated PAHs are quickly destroyed through C 2 loss (or isomerized to cages and fullerenes) by further UV photon absorption (Joblin 2003;Zhen et al 2014) and this is expected to be the dominant photo destruction route for small PAHs (Berné & Tielens 2012;Montillaud et al 2013). Hence, as small dehydrogenated PAHs are quickly destroyed, the I 6.2 /I 11.3 µm band ratio would show little variation.…”
Section: General Description Of Pah Modelmentioning
confidence: 99%
“…The hydrogen coverage on a PAH is a balance between dehydrogenation of highly excited PAHs following UV absorption and hydrogenation reactions with atomic hydrogen (Tielens et al 1987;Le Page et al 2003). Theoretically and experimentally, it has been well established that dehydrogenation is an "on/off" switch; for example, when dehydrogenation becomes important, a PAH quickly loses all its hydrogens; over a small range of G 0 /n H (Ekern et al 1997;Tielens 2005;Berné & Tielens 2012;Zhen et al 2014). Hence, for any PAH, there is a critical G 0 /n H ratio and a PAH becomes fully hydrogenated (completely dehydrogenated) if the G 0 /n H ratio is less (larger) than this ratio.…”
Section: General Description Of Pah Modelmentioning
confidence: 99%
“…Thus, we obtain that the ionization fraction of C 60 is 38%. If we consider a maximum abundance of C 60 in NGC 7023 of 1.7 × 10 −4 of the elemental carbon (Berné & Tielens 2012), this implies an abundance of ∼1.0 × 10 −4 of the elemental carbon abundance for C + 60 . This is a factor at least 10 lower than the value derived by Foing & Ehrenfreund (1994) for the diffuse interstellar medium, assuming that C + 60 is the carrier of the two DIBs at 9577 and 9632 Å.…”
Section: Abundancementioning
confidence: 99%
“…In the NGC 7023 reflection nebula, Sellgren et al (2010) have shown that C 60 is predominantly found in the regions closest to the star. In that part of the nebula, UV irradiation is high (above 10 4 times the interstellar standard radiation field), and PAH molecules are ionized (Rapacioli et al 2005;Berné et al 2007;Pilleri et al 2012), if not destroyed (Berné & Tielens 2012;Montillaud et al 2012). One could therefore expect C + 60 to be present in these regions.…”
Section: Introductionmentioning
confidence: 99%